2016
DOI: 10.5115/acb.2016.49.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study on the infraorbital foramen in relation to sex and side of the cranium in northeastern Brazil

Abstract: Detailed knowledge of the possible anatomical and morphometric variations of the infraorbital foramen (IOF) is important for ensuring safe and successful regional anesthesia, and for avoiding iatrogenic nerve injuries during surgery on the middle third of the face. To conduct a morphometric study on the IOF, correlating this with sex and side of the cranium. Two hundred forty-two crania were used (148 male and 94 female). Measurements were made with the aid of digital calipers with precision to 0.01 mm. Presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…These finding are in agreement with those reported in previous studies [11, 12, 24]. However, contrary to these findings, Agthong et al [6] and Cisneiros de Oliveira et al [15] reported that the values observed for the distance from the IOF to ANS varied significantly between the sexes and sides of the crania.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These finding are in agreement with those reported in previous studies [11, 12, 24]. However, contrary to these findings, Agthong et al [6] and Cisneiros de Oliveira et al [15] reported that the values observed for the distance from the IOF to ANS varied significantly between the sexes and sides of the crania.…”
Section: Discussionsupporting
confidence: 91%
“…The mean distances of the IOF-IOM in the present study, 6.52 ± 2.03 mm and 7.30 ± 1.57 mm on the right and left sides, respectively, are comparatively similar to those reported by Boopathi et al [14] and Gupta [22] in Indian populations but higher values have been reported in other studies [3, 5, 9, 13, 15]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The IOF is an important structure in the maxillofacial area where the infraorbital artery and nerve pass. These structures supply various areas in the face [12]. The foramina demonstrate morphologic variations between different populations [13].…”
Section: Discussionmentioning
confidence: 99%
“…The foramina demonstrate morphologic variations between different populations [13]. Thus, it is essential for surgeons and anesthesiologists to have exact knowledge of the location of the IOF before any procedure [12]. Various anatomic landmarks are used in several studies to identify its location and help surgeons in reconstructive and orthognathic surgeries, as well as while performing a nerve block [11].…”
Section: Discussionmentioning
confidence: 99%